The Effectiveness of Implementing the Quality Management System ISO 9001; 2015 in Supervising Road and Bridge Projects in South Sulawesi Province - Muhammad Tahrir; Mika Debora Br Barus (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
ISO 9001;2015 Quality Management System is a quality assurance document for the stages of the process of implementing construction work activities in accordance with management rules. There are 7 ISO 9001;2015 principles, namely: 1. Customer focus, 2. Leadership, 3. Engagement and competence of people, 4. Process approach, 5. Improvement, 6. Informed decision making, 7. Relationship management. This study aims to examine the effectiveness of implementing the ISO 9001;2015 Quality Management System in fulfilling quality management requirements in the implementation of supervision on road and bridge projects in South Sulawesi province based on the seven principles of ISO 9001;2015. Data collection was carried out by interviewing, observing and distributing questionnaires to Supervision Consultant personnel in all road and bridge monitoring packages in the province of South Sulawei for the 2022 fiscal year. To analyze the effectiveness of implementing the Quality Management System ISO 9001; 2015 a quantitative descriptive approach was used and analysis used a Likert scale, the type of data used is primary data (results of interviews, questionnaires, observations) and secondary data. Based on the research results, the effectiveness of implementing ISO 9001; 2015 in project implementation is in the good category.